(untitled) (International journal of artificial intelligence, 2025)
The preparation of individual wrestlers for competition involves both physical and psychological components that are critical to optimal performance. Physical preparation focuses on strength, endurance, flexibility, agility, and injury prevention through structured training routines, including strength training, conditioning, flexibility exercises, and recovery strategies. Psychological preparation addresses mental toughness, focus, stress management, and cognitive skills, which are essential for wrestlers to perform under pressure and maintain concentration during matches. A pre-competition routine that includes tapering, mental rehearsal, and optimal weight management is also necessary to ensure readiness. Together, physical and psychological preparation enhance a wrestler's ability to compete successfully and consistently achieve peak performance.